Effects of entresto on ejection fraction, and the effects of selected demographic and clinical variables, and the effects of titrated entresto dose on ejection fraction - Mooney, Mary (My University, 2024)
Administration of Entresto made a positive difference to the EF. Age, myocardial infarction history, pre Entresto EF, and maximum dosage of (97/103) were significantly associated with the output variables. Where possible, rapid up-titration should be aimed for. Larger studies would help identify additional predictors.
Irish Cardiac Society and Irish Nurses Cardiovascular association
Keywords: Acute care nursing; Health outcomes; Nursing